Multi-layered LiNbO3 films prepared by a polymeric precursor method - Bouquet, V; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Viry, M. G.; Perrin, A. (Elsevier B.V., 2001)
The polymeric precursor method was used to prepare multi-layered LiNbO3 films. The overall process consists of preparing a coating solution from the Pechini process and the deposited film is subsequently heat-treated. Two-layered films were prepared by this process, onto (0001) sapphire substrates. Two different routes were investigated for the heat-treatment. The amorphous route consisted of performing, after each deposition, a pre-treatment at low temperature to eliminate the organic material. In this case, the crystallization heat-treatment was performed only after the two layers had been deposited. on the other hand, a process layer-after-layer crystallization was used. Both routes led to (0001) LiNbO3 oriented films. However, only the film prepared by the layer-after-layer crystallization presented an epitaxial growth and a crack-free morphology. Moreover, the layer-after-layer crystallization process led to a film exhibiting the best optical properties. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: films; microstructure-final; niobates; optical properties